PREVALENSI DAN FAKTOR RISIKO HIPERTENSI DERAJAT 2 DI WILAYAH KERJA PUSKESMAS POASIA KOTA KENDARI - Asriah Septiawati Jabani; Adius Kusnan; I Made Cristian B (NHM PRESS, 2021)
Hypertension is one of the main cardiovascular risk factors which is the cause of premature death in the world community. Hypertension is dangerous for the elderly. The elderly often do not know that they are people with hypertension, it is only known after examination of other diseases or organ damage has occurred. Organ damage is the target as a result of the large increase in the degree of blood pressure that is not controlled and who does not receive treatment so that the elderly need to control their blood pressure. The purpose of this study was to determine the risk factors for hypertension in the working area of the Poasia Public Health Center, Kendari City. This type of research is analytic observational with a case control study design with a sample of 117 respondents consisting of 39 cases and 78 controls in the working area of the Poasia Public Health Center, Kendari City. Data analysis used chi square test for bivariate analysis and binary multiple logistic regression with enter method for multivariate analysis. The results showed that the risk factors of physical activity, consumption of salt, consumption of fruits and vegetables and stress, affect the incidence of hypertension in the elderly with grade 2 at the Poasia Public Health Center, Kendari City. The most dominant risk factor is salt consumption with a large risk value of aOR = 21,838 with a confidence interval (95% CI =1,838-2,896,410). It is hoped that the government can overcome the problem of hypertension through intervention on risk factors by monitoring blood pressure and educating families and hypertension patients, stress screening and promoting active exercise programs and optimizing counseling about hypertension diet.